An Analysis of Students’ Reading Interest in Islamic Literature at the Library of SMK Negeri 1 Pringapus - Gris dianto; Zaenal Abidin; Isnaini (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to analyze students’ reading interest in Islamic literature at the library of SMK Negeri 1 Pringapus, Semarang Regency. Islamic literacy in schools plays a crucial role in deepening religious understanding while also supporting students’ character development. However, technological advancements and shifts in students’ learning patterns have contributed to the declining use of library resources, including Islamic reading materials available in school libraries. This research employed a descriptive qualitative approach with a field study design. Data were collected through observations of students’ activities in the library, interviews with students, Islamic Education teachers, and librarians, as well as documentation related to library collections and school literacy programs. Data analysis was conducted through the processes of reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the phenomenon under study. The findings indicate that students’ reading interest in Islamic literature remains relatively low. This condition is influenced by the limited availability of collections that align with students’ needs, suboptimal library management and services, and the absence of consistent reading habits. In addition, the lack of integration between library literacy programs and Islamic Education learning activities has further affected the utilization of Islamic literature. This study highlights the importance of strengthening library management, developing contextualized collections, and fostering collaboration between teachers and librarians to enhance students’ reading interest and Islamic literacy.